LUAS PENGUNGKAPAN TATA KELOLA PERUSAHAAN PADA BANK SYARIAH DI INDONESIA - Rizki Amalia Elfita; Heni Agustina (Jurnal Bisnis dan Keuangan, 2020)
The purpose of this study is to empirically test the influence of the size of Islamic banks, Muslim board of director proportion, and sharia supervisory boards on the broad disclosure of corporate governance. The population in this research is a sharia banking company in Indonesia in 2015 to 2018 with a total of 44 company data. The sample was selected using a purposive sampling method. The data used in this study were analyzed using multiple linear regression analysis. Multiple linear regression analysis was carried out with the help of SPSS 25.0 software. The results of the study showed that there were 41 data samples of sharia bank companies in Indonesia that met the criteria of purposive sampling which assigned in this research. The results of this research prove that the size of Islamic banks, Muslim board of director proportion, and sharia supervisory boards were positively influenced the broad disclosure of corporate governance.